Reasoned Space - Druckrey, Timothy (Tucson : Center for Creative Photography/University of Arizona, 1980)
Denes, Agnes ; Dibbets, Jan ; Huebler, Douglas ; Kasten, Barbara ; Le Va, Barry ; LeWitt, Sol ; Oppenheim, Dennis ; Pfahl, John ; Smithson, Robert ; Alan Sonfist ; Vazan, Bill
Reasoned Space, Center for Creative Photography/University of Arizona, Tucson, 1980
boek